CODE MIXING IN ENGLISH COURSE LEARNING IN THE PHARMACY UNDERGRADUATE STUDY PROGRAM AT INSTITUT KESEHATAN HELVETIA MEDAN - Horia Siregar; Munawaroh Munawaroh; Mariana Mariana; Rudi Purwana (Journal Analytica Islamica, 2025)
This study explores the use of code-mixing in English language learning within the Pharmacy Undergraduate Program at Institut Kesehatan Helvetia Medan in 2024. Code-mixing, which involves blending elements from two or more languages within a single utterance, is considered to enhance communication effectiveness between lecturers and students. Previous research has indicated that this strategy can support vocabulary acquisition and improve overall English language skills. The research focuses on the types of code-mixing frequently employed, students' perceptions of this practice, and its impact on their comprehension of the material as well as their English proficiency. A descriptive qualitative approach is applied, with data collected through observation and audio recordings. Data analysis involves reduction, display, and conclusion drawing to gain an in-depth understanding of this phenomenon.